2021
DOI: 10.3390/plants10122591
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Stages-Specific Response of Anise Plants to Laser-Induced Growth, Nutrients Accumulation, and Essential Oil Metabolism

Abstract: Compared to seeds and mature tissues, sprouts are well known for their higher nutritive and biological values. Fruits of Pimpinella anisum (anise) are extensively consumed as food additives; however, the sprouting-induced changes in their nutritious metabolites are hardly studied. Herein, we investigated the bioactive metabolites, phytochemicals, and antioxidant properties of fruits, sprouts (9-day-old), and mature tissue (5-week-old) of anise under laser irradiation treatment (He-Ne laser, 632 nm). Laser trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…Earlier, laser light improved the levels of essential oils and their precursors in anise [ 52 ] which supports our results. Moreover, Balkhyour et al (2021) [ 53 ] reported an induced accumulation of essential oils, phenylalanine, and cinnamic acid in He-Ne laser-treated ajwain seedlings, which is also in agreement with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Earlier, laser light improved the levels of essential oils and their precursors in anise [ 52 ] which supports our results. Moreover, Balkhyour et al (2021) [ 53 ] reported an induced accumulation of essential oils, phenylalanine, and cinnamic acid in He-Ne laser-treated ajwain seedlings, which is also in agreement with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…The mobile phase was water:formic acid (90:10 (v/v)), and acetonitrile:water:formic acid (85:10:5 (v/v/v)) at the flow rate of 1 mL/min and oven temperature 30 • C. The elution with linear gradients was from 5% to 30% B in 40 min, from 30% to 50% B in 20 min, and from 50% to 80% B in 10 min. The detection of each compound's concentration was done using a calibration curve of the corresponding standard [20]. About 13 standards were used with high purity and bought from Sigma-Aldrich, i.e., syringic acid, gallic acid, ferulic acid, p-coumaric acid, vanillic acid, caffeic acid, ellagic acid, apigenin, quercetrin, luteolin, naringenin, myricetin, quinol, pyrogallol, and quercetin.…”
Section: Hplcmentioning
confidence: 99%
“…To the author's best knowledge, no research data are available in the literature covering microgreens cultivation of anise, caraway, and chervil, and the literature on dill is scarce. Caraway, anise, and dill for example were examined for their phenolic profile and antioxidant activity but only as sprouts [16][17][18]. Therefore, based on the aforementioned considerations, these species were assessed in this study as microgreens and characterized for their content of macrominerals (P, K, Ca, Mg, Na), microminerals (Fe, Mn, B, Zn, Se), pigments (total chlorophylls, lutein, β-carotene), total ascorbic acid, phenolic profile, and antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%